Preparation of hapten and immunogen for producing polyclonal antibody specific to cypermethrin - Hongsibsong S. (2014)
This study aimed at developing a method for the preparation of hapten and immunogen for producing polyclonal antibody specific to cypermethrin for the determination of insecticide residues in contaminated fruits and vegetables. 3-(2, 2-dichlorovinyl)-2, 2-dimethyl - (1-cyclopane) carboxylic acid (DCCA) was used as a spacer arm of hapten preparation. DCCA was linked to beta alanine methyl ester and conjugated with bovine serum albumin (BSA) as an immunogen and with oval albumin (OVA) as a coating antigen. BALB/c mice were immunized with immunogen. After three doses, sera from each mouse were collected and used to develop an ELISA. 0.05% Tween20/PBS with 20% methanol was used as diluents. The obtained polyclonal antibody (pAb) gave IC50 to cypermethrin at 5.2 μg/well. The lowest quantification limit of detection of the ELISA was 0.18 μg/well at 85% B/B0 and the detection limit was 0.039 μg/well at 90% B/B0. The antibody will be applicable for developing ELISA for screening of cypermethrin residue in vegetable and fruit samples and enable to save cost of currently used analytical procedures. © 2012 Friends Science Publishers.